Ìstoričnì peredumovi viniknennâ ta rozvitku korupcїї âk antisocìal′nogo âviŝa - Kovnij, Ûrìj (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article investigates the origins of corrupt relationships whose foundation can be found even at the biological stage of the development of nature and human. Corruption existed in every society in all periods of human history. Complaints that the world will be destroyed because of bribery and corruption were commonplace, e.g. on a Assyrian clay tablet in 2800 BC. People, who were dependent on the forces of nature, and grace of their leaders, have always tried to appease them and brought gifts bribery, in other words — committed active corruption. An expensive gift was profitable and identified a person among the applicants which was a guarantee that his request will be fulfilled.It should be noted that at this stage a gift bribe cannot be considered as a harmful phenomenon, it plays a positive role as exempting people who manage a separately formed society from everyday domestic concerns. The person who brings the gift cannot expect a favorable response, they can only hope for it.This allows us to draw some conclusions: corruption is a prerequisite for the possibility of obtaining benefits depending on the social status; relations in the form of a gift bribe did not constitute socially harmful acts, but rather were permitted and encouraged by the rules of morality.Details of corruption contained in historical sources from ancient eastern civilizations — ancient Egypt, China, India and the antique civilizations of Ancient Greece and Rome. Corruption as a negative phenomenon can be found in the Old Testament: “For I know your crimes are many and your sins innumerable. They oppress the righteous, take a bribe, and deprive the poor of justice at the gates.Attainment of benefits requires certain resources costs, compensated by funds received from consumers of those goods. Salaries of employees belong to the costs borne by the consumer through payment of required fees, but their activity is determined by the will of the authorities and employers. This leads to a situation where the consumer receives the required service or product from the employee, but cannot directly influence their activities.With the appearance of the state and the emergence of professional bureaucrats, tradition to endow those on whom one’s fate dependent has spread.At present, the cause of this antisocial phenomenon depends on the status of property rights: the poorer and socially protected the population, the higher the level of corruption. Therefore, the best and safest way to fight corruption is to increase the level of social wealth.Acts of corruption in the public sector are one of the major problems of our time, the successful solution to which, based on the analysis of historical experience, will make it easier to facilitate the successful development of the state and society as a whole.
Keywords: corruption; official; gift; bribe